A combination of supraglottic airway and bronchial blocker for one-lung ventilation in infants undergoing thoracoscopic surgery. Issue 2 (February 2023) - Lv, Junlin; Ding, Xiaoying; Zhao, Jing; Zhang, Huijuan; He, Jiaojiao; Ma, Lei; Lv, Jianrui
Abstract: Objectives: One-lung ventilation (OLV) for children under the age of two years is difficult. The authors hypothesize that a combination of a supraglottic airway (SGA) device and intraluminal placement of a bronchial blocker (BB) may provide an appropriate choice. Design: A prospective method-comparison study. Setting: Second Affiliated Hospital of Xi'an Jiaotong University, China. Participants: 120 patients under the age of two years undergoing thoracoscopic surgery with OLV. Interventions: Participants were randomly assigned to receive intraluminal placement of BB with SGA (n = 60) or extraluminal placement of BB with endotracheal tube (ETT) (n = 60) for OLV. Measurements and main results: The primary outcome was the length of postoperative hospitalization stay. The secondary outcomes were the basic parameters of OLV and investigator-defined severe adverse events. The postoperative hospitalization stay was 6 days (interquartile range, IQR 4–9) in SGA plus BB group compared with 9 days (IQR 6–13) in ETT plus BB group ( P  = 0.034). The placement and positioning duration of SGA plus BB was 64 s (IQR 51–75) compared with 132 s (IQR 117–152) of ETT plus BB ( P  = 0.001). The values of leukocyte (WBC) and C-reactive protein (CRP) of SGA plus BB group on the first day of post-operation were 9.8 × 10 9 /L (IQR 7.4–14.5) and 15.1 mg/L (IQR 12.5–17.3) compared with 13.6 × 10 9 /L (IQR 10.8–17.1) and 19.6 mg/L (IQR 15.0–23.5) of ETT plus BB group ( P  = 0.022 and P  = 0.014). Conclusion: There were few if any significant adverse events in the intervention group (SGA plus BB) for OLV in children under the age of two years, and this method seems worthy of clinical application. Meanwhile, the mechanism for this novel technique to shorten the length of postoperative hospitalization stay needs to be further explored.